2011
DOI: 10.1016/j.jaapos.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and quality of nonmydriatic fundus photography in children

Abstract: Purpose Ocular funduscopic examination is difficult in young children and is rarely attempted by nonophthalmologists. Our objective was to determine the feasibility of reliably obtaining high-quality nonmydriatic fundus photographs in children. Methods Nonmydriatic fundus photographs were obtained in both eyes of children seen in a pediatric ophthalmology clinic. Ease of fundus photography was recorded on a 10-point Likert scale (10 = very easy). Quality was graded from 1 to 5 (1, inadequate for any diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Non-mydriatic fundus photography also shows promise in this area. In one recent study, 15 the use of a non-mydriatic digital fundus camera allowed for the acquisition of fundus photographs of satisfactory quality in children over the age of 3 years and in some children as young as 22 months, without pupillary dilation.…”
Section: Retinal Photography As a Diagnostic Toolmentioning
confidence: 99%
“…Non-mydriatic fundus photography also shows promise in this area. In one recent study, 15 the use of a non-mydriatic digital fundus camera allowed for the acquisition of fundus photographs of satisfactory quality in children over the age of 3 years and in some children as young as 22 months, without pupillary dilation.…”
Section: Retinal Photography As a Diagnostic Toolmentioning
confidence: 99%
“…In fact, ophthalmologists sometimes have difficulty visualizing the fundi of young, uncooperative patients despite pupillary dilation. In a recent study of 212 children (median age, 6 years; range, 1–18 years), 31 non-mydriatic photographs of at least one eye were obtained in 190 children (89.6%) and in both eyes in 181 (85.3%). The study found that it was feasible to obtain non-mydriatic fundus photographs of adequate quality in children >3 years of age and in children as young as 22 months.…”
Section: The Presentmentioning
confidence: 99%
“…Since the American Academy of Pediatrics states that direct ophthalmoscopy “may be possible to perform in very cooperative 3 to 4 year olds”, 32 the study authors suggested that non-mydriatic fundus photography may expand the age range of children who can have an evaluation of the ocular fundus areas generally visualized by direct ophthalmoscopy to almost all 3-year-olds and some cooperative 2-year-olds. 31 …”
Section: The Presentmentioning
confidence: 99%
“…5 Dr. Subhakaran touches on many important advantages of nonmydriatic fundus camera over direct ophthalmoscopy, including better diagnostic accuracy, lower risk of medico-legal liability, objective recording for future comparison, and possibility of telemedicine. We showed that nonmydriatic fundus photographs have a role in the acute evaluation of neurologic conditions, 1 but their use may be extended to many other medical settings, such pediatric ophthalmology 6 or even infectious diseases in endemic areas as described by Dr. Subhakaran. Nonmydriatic fundus photographs have numerous assets and may become the gold standard for funduscopic evaluation for tomorrow's nonophthalmologist care providers.…”
mentioning
confidence: 99%